Unrecognized role of claudin‐10b in basolateral membrane infoldings of the thick ascending limb. Issue 1 (22nd August 2022) - Quintanova, Catarina; Himmerkus, Nina; Svendsen, Samuel L.; von Schwerdtner, Otto; Merkel, Cosima; Pinckert, Lennart; Mutig, Kerim; Breiderhoff, Tilman; Müller, Dominik; Günzel, Dorothee; Bleich, Markus
Abstract: Claudin‐10b is an important component of the tight junction in the thick ascending limb (TAL) of Henle's loop and allows paracellular sodium transport. In immunofluorescence stainings, claudin‐10b–positive cells exhibited extensive extra staining of basolateral, column‐like structures. The precise localization and function have so far remained elusive. In isolated cortical TAL segments from C57BL/6J mice, kidney‐specific claudin‐10 knockout mice (cKO), and respective litter mates (WT), we investigated the localization and protein expression and function by fluorescence microscopy and electrophysiological measurements. Ultrastructural analysis of TAL in kidney sections was performed by electron microscopy. Claudin‐10b colocalized with the basolateral Na + ‐K + ATPase and the Cl – channel subunit barttin, but the lack of claudin‐10b did not influence the localization or abundance of these proteins. However, the accessibility of the basolateral infolded extracellular space to ouabain or fluorescein was increased by basolateral Ca 2+ removal and in the absence of claudin‐10b. Ultrastructural analysis by electron microscopy revealed a widening of basolateral membrane infoldings in cKO in comparison to WT. We hypothesize that claudin‐10b shapes neighboring membrane invaginations by trans interaction to stabilize and facilitate high‐flux salt transport in a water‐tight epithelium. Abstract : Claudin‐10b is an important component of the tight junction in the thick ascending limb (TAL) of Henle's loop and allows paracellular sodium transport. In immunofluorescence stainings, claudin‐10b–positive cells exhibited extensive extra staining of basolateral, column‐like structures. The precise localization and function have so far remained elusive. In isolated cortical TAL segments (cTALs) from C57BL/6J mice, kidney‐specific claudin‐10 knockout mice (cKO), and respective litter mates (WT), we investigated the localization and protein expression and function by fluorescence microscopy and electrophysiological measurements.